Analisis Kualitas Produk Dan Harga Terhadap Citra Perusahaan Dan Kepuasan Konsumen Berdampak Pada Loyalitas Perusahaan Sari Jati Kabupaten Sragen - Septiana Novita Dewi (Universitas Mercu Buana Yogyakarta, 2014)
This study aims to determine the empirical analysis of the quality of the product and the price of the company's image and customer satisfaction impact on the company's loyalty Sari Jati Sragen. The analytical method used is by using validity and reliability test, path analysis, t test, F test, and test the coefficient of determination. The population in this study is that consumers in the company Sari Jati in the regency number of 900 consumers 2014. The sample in this study is 10% of the population is equal to 90 consumers. The results of t-test on the first equation can be concluded that the variable quality of the product and a significant positive effect on consumer satisfaction. Variable rates and no significant positive effect on satisfaction. The results of t-test on the second equation can be concluded that the variable quality of the product and price positive and significant impact on the image of the company. The results of t-test on the third equation can be concluded that the quality of the product, price, customer satisfaction and corporate image and a significant positive effect on loyalty. F test results can be concluded jointly independent variable affects loyalty. R2 value of 0.994 means the total variation in the Company's customer loyalty Sari Jati Sragen explained by the variable quality of the product, price, customer satisfaction, corporate image and amounted to 99.4% and the remaining 0.6% is explained by other variables outside the model study.